The Effect of Work Motivation on Employee Performance in the Production Department at PT GARUDA TOP PLASINDO in Surabaya - shindu dedali (Jurnal Penelitian Ekonomi dan Akuntansi (JPENSI), 2023)
PT GARUDA TOP PLASINDO in Surabaya expects a quality workforce along with technological developments and in line with efforts to motivate employees to improve their performance. Based on the research that has been carried out, the analysis obtained by the author is the relationship with work motivation on employee performance. From these problems, the authors write the problem is: "how much influence does work motivation have on the performance of production employees at PT GARUDA TOP PLASINDO in Surabaya. The purpose of this study is to determine the factors that can motivate employees' work, so that employee performance can be improved. The hypothesis that can be put forward in relation to the formulation of the problem is that work motivation has a positive effect on employee performance at PT GARUDA TOP PLASINDO in Surabaya.The variables studied were (X) work motivation and (Y) employee performance. Variables (X) that are measured include incentives, salary, work environment, and career paths, while variables (Y) that are measured include work performance, company loyalty, quantity of work and quality of work. From the results of the correlation calculation, it is obtained (R) of 0.991, which means that the correlation coefficient is positive, which can also mean that there is a direct relationship between the two variables or a very strong relationship between the two variables. The results of the calculations obtained the multiple regression equation as follows: y = 21.563 + 1.442 x1 + 1.958 x2 + 2.947x3 + 2.437x4, meaning that if the independent variables X1, X2, X3, X4 increase by one unit, the employee's performance will increase by 1.442, 19.958, 2.947, 2.437 units assuming other variables are constant.